PEMBERIAN KOMBINASI PUPUK LIMBAH CAIR BIOGAS DENGAN PUPUK KANDANG AYAM PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Luberius, Ari; Yoseva, Sri; ', Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Good organic material used as fertilizer is bioslurry and chicken manure fertilizer, bioslurry fertilizer will be maximized when combined with chicken manure fertilizer as chicken manure fertilizer has advantages over other animal manures. This research aims to determine the effect of bioslurry fertilizer combination with chicken manure fertlizer and get the best treatment combination in oil palm seed in main nursery. This experiment using a Completely Randomized Design (CRD). Consists of 10 treatments and 3 replications combination, in order to obtain 30 units of experiments, each unit consist of 2 plants. The treatments are: P0: bioslurry fertilizer 0 ml with chicken manure fertilizer 0 g, P1: 100 ml with 0 g, P2: 200 ml with 0 g, P3: 300 ml with 0 g, P4: 100 ml with 50 g P5: 200 ml with 50 g, P6: 300 ml with 50 g, P7: 100 ml with 100 g, P8: 200 ml with 100 g, P9: 300 ml with 100 g. Parameter observed were : the seeds height, number of leaves, stump diameter, root volume, root crown ratio and seeds dry weight. The results of research indicated the combination of bioslurry fertilizer application with chicken manure fertilizer real effect on all parameter of seeds height and seeds root volume. Combination of 200 ml biogas fertilizer with 100 g chicken manure fertilizer is the best combination of all parameter. Keywords: Bioslurry fertilizer, chicken manure fertilizer, oil palm seed